Developing the Counsellor as Teacher: A Systematic Program - Katz, Judy H.; Ivey, Allen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The need to expand counselling services beyond the remedial one-to-one relationship is becoming widely recognized. The concept of counsellor-as-teacher has gained popularity as a developmental approach to helping people achieve interpersonal competence. This article describes a systematic training program designed to help counsellors transfer their skills to the classroom and thus become teachers of interpersonal effectiveness.